التأثير الاقتصادي لزراعة التبغ في الساحل السوري على المزارعين والمؤسسة العامة للتبغ - صقر, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Tobacco cultivation is one of the most important crops in the world due to the increase in consumption and the continuous and increasing demand for this product The Syrian coast has been a pioneer in this agriculture since ancient times and still constitutes a large proportion of farmers' income. It absorbs part of the surplus labor, which can be cultivated by most members of the family. The General Organization of Tobacco is the only institution that can grant licenses and purchase the production of farmers and manufacture and export, which sets prices regardless of the mechanism of the market, which is a problem for farmers, where the purchase of production at low prices is not commensurate with the costs and effort. Although the price of raw tobacco purchased by farmers increases during the 2017-2018 season, the difference still exists between this price and costs. For some species production costs are higher than the price offered by the price of 300 SYP. تعتبر زراعة التبغ من الزراعات الهامة جداً على مستوى العالم بسبب التزايد في الاستهلاك والطلب المستمر والمتزايد على هذا المنتج. وقد كان الساحل السوري رائداً في هذه الزراعة منذ القدم وما زال, وهو يشكل نسبة كبيرة من دخل المزارعين, كما أنه يمتص جزء من فائض العمالة, حيث يستطيع أن يعمل بزراعته معظم أفراد العائلة. وتعتبر المؤسسة العامة للتبغ المؤسسة الوحيدة التي يمكنها منح الرخص وشراء الإنتاج من المزارعين وتصنيعه وتصديره, وهي التي تحدد أسعاره بغض النظر عن آلية السوق, وهذا ما يشكل مشكلة لدى المزارعين حيث يشترى منهم الإنتاج بأسعار منخفضة لا تتناسب مع التكاليف والجهد المبذول. ورغم زيادة أسعار التبغ الخام المشترى من المزارعين خلال موسم 2017 ـ 2018, إلا أن الفارق مازال موجوداً بين هذا السعر والتكاليف, حيث تزيد تكاليف الإنتاج بالنسبة لبعض الأنواع عن السعر المقدم بمقدار (300) ل.س.